2019
DOI: 10.1177/1086296x19839181
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Children’s Literature in Cultivating Preservice Teachers as Transformative Intellectuals: A Literature Review

Abstract: This review of literacy education scholarship examines the ways that children’s literature is used as a resource within literacy methods courses in the preparation of preservice teachers (PTs) as transformative intellectuals. The research indicates that the use of children’s literature in literacy methods courses has served two distinct purposes: (a) to engage PTs in learning literacy instructional practices and (b) to engage PTs in building sociocultural knowledge and learning transformative (e.g., culturally… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(41 citation statements)
references
References 35 publications
0
40
0
1
Order By: Relevance
“…Similarly, much of the research in these syntheses looked at preservice teacher preparation in a single semester and in one context, rather than across time and space (see Fowler‐Amato, LeeKeenan, et al, 2019; Hoffman et al, 2019). Finally, as a way of radically reimagining literacy instruction in teacher education (Sailors, 2019), the work of Flores et al (2019) and Mosley Wetzel et al (2019) suggested that research in literacy teacher education should be used to dismantle hegemony.…”
Section: Research On Literacy Teacher Preparationmentioning
confidence: 99%
“…Similarly, much of the research in these syntheses looked at preservice teacher preparation in a single semester and in one context, rather than across time and space (see Fowler‐Amato, LeeKeenan, et al, 2019; Hoffman et al, 2019). Finally, as a way of radically reimagining literacy instruction in teacher education (Sailors, 2019), the work of Flores et al (2019) and Mosley Wetzel et al (2019) suggested that research in literacy teacher education should be used to dismantle hegemony.…”
Section: Research On Literacy Teacher Preparationmentioning
confidence: 99%
“…There is a growing appreciation of the role children's literature can play in supporting teacher trainees to recognize a multiplicity of linguistic resources, acknowledge cultural and socioeconomic differences, and respond to the varied literacy needs of learners in classroom contexts [23,45,46]. Bishop's [47,48] use of the mirrors and windows metaphor highlights the potential of children's literature to serve as a powerful resource to teach about dimensions of diversity and cultural representation.…”
Section: Engagement With Children's Literature: An Integral Part Of Lmentioning
confidence: 99%
“…Within the context of this paper, critical texts refers to texts that actively take up issues of difference and dimensions of race, ethnicity, gender identity, class, or linguistic diversity. Relevant research reveals that LTEs have used children's literature to create spaces of learning, which encourage teacher trainees to consciously reflect upon categories of difference, to inquire into multiple perspectives, and to actively explore the relationship between language, culture and identity [45,[51][52][53][54][55][56][57]. These spaces of learning can encourage teacher trainees to engage in conversations that centre marginalized voices and a range of lived experiences.…”
Section: Engagement With Children's Literature: An Integral Part Of Lmentioning
confidence: 99%
See 2 more Smart Citations